DEVELOPMENT OF ANIMATION MEDIA TO IMPROVE STUDENTS’ LEARNING MOTIVATION AND CHEMISTRY LEARNING ACHIEVEMENT AT SMAN 4 PRAYA - Zar’atul Muhsinin; H. Wildan; Muntari Muntari (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2013)
This study aims to develop chemistry animation media of redox reactions. The study was conducted by using the approach of R & D by Borg & Gall including preliminary study, early product development, validation, limited testing, product revision, and the testing stage. To examine the effectiveness of media on students’ motivation and learning outcomes using the stages of classroom action research (CAR) was conducted at SMAN 4 Praya. Data of the study was collected through activity observation, questionnaires, and achievement test. Based on the result, it can be concluded that students’ cognitive achievement hasclassical completeness by 61% in cycle 1 and 78 % in cycle 2. The average of students’ motivation also improveby 69 in cycle 1 and  by 75 in cycle 2 although both are included in the middle category.